Analisis Pengaruh Penyesuaian Nilai Jual Objek Pajak (NJOP) Terhadap Kemauan Wajib Pajak Membayar Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Kabupaten Mimika - Maharani, Dina Vika; Padang, Nely Salu (STIE Jambatan Bulan, 2023)
This study aims to determine the effect of selling price adjustments Tax Object Against Willingness of Taxpayers in Paying Land Tax and Rural and Urban Buildings (PBB-P2) in Mimika Regency. The research method used in this study is method associative research. The analysis used descriptive analysis for determine the taxpayer's response to the NJOP adjustment and chi squere analysis to determine the effect of the NJOP adjustment on the willingness of the taxpayer taxes pay taxes. The data used is qualitative data and quantitative data, which was collected using documentation and questionnaires. Resultsresearch shows that there is a neutral response for the community regarding NJOP adjustments and the effect of NJOP adjustments on willingness of taxpayers to pay taxes shows that taxpayers in Mimika Regency is aware of its obligation to pay taxes